Fuel Availability and Java Households Cooking Fuel Choices: Evidence from Indonesia’s LPG Subsidy Policy - Lestarianingsih, Restu; Adrison, Vid (Jurnal Ekonomi & Studi Pembangunan, 2021)
In 2007, Indonesia launched a 3 kg Liquified Petroleum Gas (LPG) cylinder for poor households, and micro-enterprises were started on Java island to reduce the burden of fuel subsidies. In its implementation, the subsidized LPG may also be used by non-target households, which has implications for the government’s fiscal burden. To avoid this, it is necessary to understand household behavior towards non-subsidized LPG choices. Household income and fuel availability determine the choice of household cooking fuel types. However, existing studies have not seen the relationship between subsidized and non-subsidized LPG as a household cooking fuel. Using rich data from the March 2018 National Socio-Economic Survey (Susenas) and the Ministry of Energy and Mineral Resources (KESDM) information, this study examined the relationship between income, subsidized LPG quota as a representation of the availability of subsidized fuel, and non-subsidized LPG choices as household cooking fuel in Java in 2018. The Multinomial Logit model's estimation results found that an increase in income and a decrease in subsidized LPG quotas were correlated with an increase in the opportunity to choose non-subsidized LPG as household cooking fuel in Java in 2018. Furthermore, this study revealed that the largest subsidized LPG users were non-poor households.